2012
DOI: 10.4028/www.scientific.net/amr.524-527.1157
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Drilling Fluid Additive from Lignosulfonate

Abstract: Nitration-oxidation lignosulfonate (NOLS) was prepared using lignosulfonate (LS) as raw material. The product was characterized by Fourier Transform Infrared spectroscopy (FT-IR). The performance as a drilling fluid additive was evaluated with regard to rhology, filtration and temperature resistance. The results showed that NOLS can improve the viscosity under room temperature, decrease the viscosity under high temperature and reduce the filtration more effectively than that of lignosulfonate, which display it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…For example, the main chemical components of lignin are lignosulfonate ( Figure 1) and alkali lignin with some surface active groups, such as hydrophilic groups of carboxyl and phenolic hydroxyl groups and hydrophobic groups of propyl and benzene rings. Thus, the lignin has become potential raw material of the green chemistry in oilfield chemicals, surfactants, environmental protection corrosion inhibitors and bitumen modification agents [5][6][7][8][9]. Zhang [10] modified the lignosulfonate with formaldehyde, and it is found that the modified hydroxymethylated lignin sulfonate had a viscosity-raising effect on the base slurry at room temperature and the effect of viscosity reduction and filtration loss after high-temperature aging.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the main chemical components of lignin are lignosulfonate ( Figure 1) and alkali lignin with some surface active groups, such as hydrophilic groups of carboxyl and phenolic hydroxyl groups and hydrophobic groups of propyl and benzene rings. Thus, the lignin has become potential raw material of the green chemistry in oilfield chemicals, surfactants, environmental protection corrosion inhibitors and bitumen modification agents [5][6][7][8][9]. Zhang [10] modified the lignosulfonate with formaldehyde, and it is found that the modified hydroxymethylated lignin sulfonate had a viscosity-raising effect on the base slurry at room temperature and the effect of viscosity reduction and filtration loss after high-temperature aging.…”
Section: Introductionmentioning
confidence: 99%